Analysis GISWAF on the Interest of Waqf Students: A Case Study on UNIDA Gontor - Afif, Mufti; Muzaki, Rofi; Sa’id, Roudhoh Hannaaris; Maulana, Hartomi (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The literacy of Indonesian society regarding waqf is still relatively low. People often confuse waqf with charity (sodaqoh) and voluntary contributions (infak). Similarly, the literacy among university students about waqf is also lacking. The GISWAF